Analysis of genetic diversity and selection characteristics using the whole genome sequencing data of five buffaloes, including Xilin buffalo, in Guangxi, China - Chen, Zhefu; Zhu, Min; Wu, Qiang; Lu, Huilin; Lei, Chuzhao; Ahmed, Zulfiqar; Sun, Junli (Frontiers in Genetics, 2023)
The buffalos are economically important livestock which renders useful services to mankind in terms of meat, milk, leather and draught. The Xilin buffalo is one of the native breeds of China. In the present study, the genetic architecture and selection signature signals of Xilin buffalo has been explored. A total of twenty five (n=25) Xilin buffalo whole genome data and data of forty six (n=46) buffaloes published data were used.The population structure analysis showed that the Xilin buffalo belong to the Middle-Lower Yangtze. The genome diversity of Xilin buffalo was relatively high. The CLR, π ratio, FST and XP-EHH were used to detect the candidate genes characteristics of positive selection in Xilin buffalo. Among the identified genes, the most of the enriched signal pathways are related to nervous system and metabolism. The mainly reported genes related to the nervous system (GRM5, GRIK2, GRIA4), reproductive genes (CSNK1G2, KCNIP4), and lactation (TP63). The results of this study are of great significance for understanding the molecular basis of phenotypic variation of related traits of Xilin buffalo and helps in future breeding and conservation programs of this important livestock genetic resource.